7x-3+9x-12-13x+5-x+12=0

Simple and best practice solution for 7x-3+9x-12-13x+5-x+12=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-3+9x-12-13x+5-x+12=0 equation:


7x-3+9x-12-13x+5-x+12=0

We simplify the equation to the form, which is simple to understand
7x-3+9x-12-13x+5-x+12=0

We move all terms containing x to the left and all other terms to the right.
+7x+9x-13x-1x=0+3+12-5-12

We simplify left and right side of the equation.
+2x=-2

We divide both sides of the equation by 2 to get x.
x=-1

See similar equations:

| 3w^2-22w-6=0 | | y=x^2-6x-10factor | | 89+k=42 | | 42n/(n+1) | | (5x+6)(5x^2-36x+36)=0 | | .75x-28.50=36.75 | | -4(2-3x)=7-2(x+3) | | -3=4x+6-1x | | 2x-8+x+10=11 | | -8(x)+23=-1 | | 4x+3x=2x+x | | 2x-5y+20=10 | | x/0.2=-2.6 | | x^3-1x^2-12x+36=0 | | x+(x-46)+(x-35)+(1/2x)=360 | | 6y^2-21=0 | | 1=-5a+1-a | | 9y-5=19y+25 | | 3(5-x)=12 | | 45+2.50x=3.75x | | -115+80=-489 | | 8s+6+5=24 | | 5x-12=12x | | 5m-9+4m=0 | | b=70-a+c | | 5y-3y-5=32.32 | | 3y-2=9y+52 | | -5(a-1)=-40 | | 15/28-5/14 | | -3/2x+27/14x=3/14 | | -20-4d=3(5d-7) | | 4x^6+7x^3-36= |

Equations solver categories